Features of the influence of seasonal variation of soil moisture on vertical movements of the earth’s surface - Павлик, В. Г.; Кутний, А. М.; Кальник, О. П.; Pavlyk, V. G.; Kutnyi, A. M.; Kalnyk, O. P. (Lviv Politechnic Publishing House, 2019)
Метою досліджень є експериментальне встановлення найсприятливіших умов визначення вертикальних рухів земної поверхні з погляду мінімального впливу варіацій вологи ґрунту на результати спостережень. Геодезичний моніторинг деформаційних процесів на геодинамічних полігонах (ГП) відбувається переважно без урахування впливу екзогенних чинників метеорологічного походження на динаміку земної поверхні та реперів. Для успішного виділення тектонічних чи техногенних рухів з усього спектра зареєстрованих переміщень земної поверхні потрібно вилучити їх гідрометеорологічну складову. Одним із видів метеорологічного впливу на динаміку земної поверхні та реперів є об’ємні деформації набряклих ґрунтів внаслідок варіації їх вологості. Вони зумовлюють сезонні вертикальні рухи, величина яких залежить від фізичних та мінералогічних властивостей ґрунту, особливостей навколишнього середовища та амплітуди річних коливань температури і вологи. Методика досліджень передбачала паралельні спостереження у двох пунктах за вертикальними рухами і вологістю верхнього однометрового шару ґрунту на ГП у Полтаві за період 2006–2015 рр. Основним результатом роботи є встановлення нелінійного характеру дії сезонних змін вологи ґрунту на вертикальні переміщення земної поверхні залежно від абсолютного значення вологості. Якщо вологість ґрунту перевищує його максимальну молекулярну вологомісткість (ММВ), то її варіації не впливають на динаміку землі. Це пояснюється різним механізмом вертикальної інфільтрації води в ґрунті залежно від його водонасиченості. У разі значної вологості ґрунту її подальші зміни зумовлені переважно капілярними та гравітаційними силами, які не викликають деформацій і вертикальних переміщень земної поверхні. Науковою новизною досліджень є встановлення важливої ролі ММВ ґрунту в генерації вертикальних рухів земної поверхні та реперів внаслідок варіацій вологи. Практична значущість роботи полягає у можливості мінімізації впливу гідрометеорологічних чинників на результати високоточних спостережень за динамікою земної поверхні. Отримані результати можна використовувати для організації високоточних спостережень за вертикальними рухами на ГП та їх інтерпретації.

The purpose of the research is to establish experimentally the most favorable conditions for determining the vertical movements of the Earth's surface in terms of the minimal influence of variations of soil moisture on the results of observations. Geodetic monitoring of deformation processes at geodynamic testing grounds (GTG) occurs mainly without taking into account the influence of factors on the dynamics of the Earth's surface and benchmarks. To successfully separate tectonic or anthropogenic movements from all recorded motions of the Earth's surface, it is necessary to exclude their hydrometeorological component. One type of meteorological impact on the dynamics of the Earth's surface and benchmarks is the volumetric deformation of the swelling soils due to the variation of their moisture. They cause seasonal vertical movements, the magnitude of which depends on the physical and mineralogical properties of the soil, the characteristics of the environment, and the amplitude of annual fluctuations in temperature and moisture. The research methodology included the parallel observations at two points of vertical movements and moisture of the top one-meter layers of soil at GTS in Poltava for the period 2006 to 2015. The main result is the determination of a nonlinear nature of the effect of seasonal changes of soil moisture on the vertical displacement of the Earth's surface, depending on the absolute values of moisture. If soil moisture exceeds its maximum molecular moisture content (MMMC), then its variations do not affect the dynamics of the ground. This is explained by the different mechanism of vertical infiltration of water in the soil, depending on its water saturation. At high levels of soil moisture, further changes are caused mainly by capillary and gravitational forces that do not cause deformations and vertical movements of the Earth's surface. The scientific novelty of this research is to establish the important role of the MMMC of soil in the generation of vertical movements of the Earth's surface and benchmarks due to variations in its moisture. The practical significance of the work lies in the possibility of minimizing the influence of hydrometeorological factors on the results of high-precision observations of the dynamics of the Earth's surface. The results obtained can be used in the organization of high-precision observations of vertical movements on the GTG and their interpretation.
Особливості впливу сезонних варіацій вологи ґрунту на вертикальні рухи земної поверхні
Keywords: повторне нівелювання; сезонні вертикальні рухи земної поверхні; вологість ґрунту; стійкість реперів; repeat leveling; seasonal vertical movements of the Earth's surface; soil moisture; benchmarks stability; 528.481; 551.242